ANALISIS PENGARUH TINGKAT INFLASI DAN SUKU BUNGA BI TERHADAP KINERJA KEUANGAN PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - B11110140, Herlina (Jurnal Manajemen Update, 2014)
This research is performed on order to test the influence of the variable Inflasi, interest rate , foreign exchange and BOPO toward the company's financial performance (Return On Equity) of Banking sector in Indonesia Stock Exchange from 2011 to 2013. Methodology research as the sample used purposive sampling, sample 19 Bank was accured 36 BankÂ  in Bursa Efek Indonesia (BEI). Data analysis with multi liniear regression and hypotheses test used t-statistic and F-statistic at level of significance 5%, a clasic assumption examination which consist of data normality test, multicolinearity test, heteroskedasticity test and autocorrelation test is also being done to test the hypotheses. During research period show as variabel and data research was normal distributed. Based on test, multicolinearity test, heterosskedasticity test and autocorrelation test classic assumption deviation has no founded, this indicate that the available data has fulfill the condition to use multi linear regression model. This result of research show that variable Inflasi, Suku Bunga SBI and Kurs did not influence ROE. Variable BOPO negative significant influence toward ROE. Prediction capability from these seven variable toward ROE is 78,6% where the balance 21,4% is affected to other factor which was not to be entered to research model. Key Words : Return On Equity (ROE), Inflation, BI Interest Rates, Kurs Valas and BOPO (Biaya Operasional/Pendapatan Operasional).